Assessing remotely sensed and reanalysis products in characterizing surface soil moisture in the Mongolian Plateau. Issue 10 (3rd October 2021) - Luo, Min; Sa, Chula; Meng, Fanhao; Duan, Yongchao; Liu, Tie; Bao, Yuhai
ABSTRACT: Soil moisture (SM) plays a crucial role in the dynamics of coupled atmosphere, water, energy, and carbon cycles. In this study, the spatiotemporal distribution and variations of SM in the Mongolian Plateau were investigated for the period of 1982–2018 based on four gridded SM datasets. Taking the observed SM from 33 monitoring stations as a reference, the reliability of these four gridded products was validated, and the three-cornered hat (TCH) method was also applied to evaluate their uncertainties. Major results indicated that all these four products underestimated the SM in this region at different levels. The ERA-Interim SM performed much better than other three products, with a higher R of 0.53 and lower ubRMSE of 0.0378 m 3 ·m −3 . Except for ECV, the surface SM exhibited a decreasing trend at −0.0004 to −0.0008 m 3 ·m −3 /decade in the warm season (from April to October) over the past 37 years. The greatest decreases in SM occurred in the summer season. Precipitation change plays a more important role in explaining the variations of SM than temperature reported by partial correlation analysis. The results of this study will benefit our understanding of the climate change effects and the protection of the ecological systems in this region.